The odd couple: diverging paths in language policy and educational practices - Prinsloo, Mastin (Faculty of Education, University of the Free State, 2011)
This paper examines the divergences between what educational policy calls for in South African schools with regard to language and learning and what takes place in schools. It argues that South African constitutional and education policy statements employ an idea of languages as bound entities and systems, and combine this understanding of languages with discourses on language rights and of language endangerment. An alternative view studied language as practice rather than system. From this perspective the idea of ‘a language’ is a misleading shorthand for a diverse range of language varieties, genres, registers and practices. Such resources are not equally distributed among users of these resources and they carry different social weightings or valuations. This paper argues that the language assumptions in language policy ‘erase’ linguistic complexities and assume a linguistic homogeneity and stability which is inappropriate. A view of language is developed where language operates as a ‘non-neutral medium’ in stratified social contexts of all kinds. These inequalities operate just as much within designated ‘languages’, in terms of the varieties and their uses within that language, as across them. The observed differences between policy prescription and language practice provide support for this alternative perspective on language.
Keywords: Language policy; Ethnography; Multilingualism; Bilingualism; Literacy